Multiculturalism in the Lower Southern Border Region: Context, History, and Sustainable Management Approaches - Dasae, Nirun; Surungkapiprat, Jirassak; Rodkhwan, Lamun (Hatyai Academic Journal, 2025)
The southern border region of Thailand is characterized by a high degree of ethnic and religious diversity, shaped by historical and geographical factors that have facilitated continuous cultural exchange. Differences in social systems, lifestyles, and economic structures have contributed to ongoing challenges in intercommunal coexistence, as well as to a sense of alienation stemming from state policies that emphasize centralized governance without adequately reflecting the needs of all population groups. This article analyzes the unique characteristics of multiculturalism in Thailand’s southern border provinces through several dimensions: a review of existing research and peace studies in the region; an examination of the historical and geographical foundations of multiculturalism; an exploration of the challenges associated with cultural diversity in the area; and the identification of strategies for managing and fostering multicultural understanding. The study emphasizes that encouraging active community participation in cultural activities that reflect the identities of diverse groups can help reduce misunderstandings and build stronger intercommunal relationships. Promoting learning about cultural differences through both formal education and community-based initiatives is essential for cultivating values of peaceful coexistence. Furthermore, the development of collaborative networks among government agencies, educational institutions, and local communities is identified as a key strategy for enhancing social harmony, mitigating conflict, and advancing sustainable development in Thailand’s southern border region.